Developing “D-A-M-E Model” For Analyzing Multifaceted Creative Communication Process In Artificial Intelligences (AI) Era - Agustina Kusuma Dewi; Adi Surahman (Universitas Budi Luhur, 2026)
Abstract Complex layers of words—images in mixed media culture has changed social norms; also the communication process. The AI era has raised the cultural gap, changing the meaning of art and design in a historical context. Although, certain cases in popular culture break this pattern, offering a timeless aesthetic appeal that transcends generations. One of them is music video